Comparison between acupuncture therapy and gabapentin for chronic pain: a pilot study. Issue 6 (December 2021) - Chen, Lucy; Deng, Hao; Houle, Timothy; Zhang, Yi; Ahmed, Shihab; Zhang, Wei; Sullivan, Shelly; Opalacz, Arissa; Roth, Sarah; Filatava, Evgenia Jen; Stabach, Kristin; Vo, Trang; et al.
Background: We examined whether the effect of true electroacupuncture on pain and functionality in chronic pain participants can be differentiated from that of medication (gabapentin) by analyzing quantitative sensory testing (QST). Methods: We recruited chronic back and neck pain participants who received six sessions (twice weekly) of true electroacupuncture versus sham electroacupuncture or 3 weeks of gabapentin versus placebo treatment. QST profiles, pain scores, and functionality profile were obtained at baseline (visit 1) and after three sessions (visit 4) or six sessions (visit 7) of acupuncture or 3 weeks of gabapentin or placebo. Results: A total of 50 participants were analyzed. We found no differences in QST profile changes (p = 0.892), pain reduction (p = 0.222), or functionality (p = 0.254) between the four groups. A major limitation of this pilot study was the limited number of study participants in each group. Conclusion: This pilot study suggests that a large-scale clinical study with an adequate sample size would be warranted to compare acupuncture and medication therapy for chronic pain management. Trial registration number: NCT01678586 (ClinicalTrials.gov).